Siyaloreli hastalara yaklaşım ve tedavi yönetimi / Approach to the patients with sialorrhea and treatment management - HASSOUNA, Hasan (My University, 2016)
Objective: Sialorrhea (drooling) is the uncontrolled and continuous release of saliva, and may be due to a range of causes. The aim of this study is to evaluate the effectiveness of bilateral submandibular duct rerouting and sublingual gland excision combined with parotid gland botulinum toxin type-A injection. Study Design: Retrospective study. Patients & Methods: This study was conducted in 13 paediatric sialorrhea patients who underwent bilateral submandibular duct rerouting and sublingual gland excision combined with parotid gland botulinum toxin type-A injection from 2012 to 2016 in Bezmialem Vakıf University, Medical Faculty, Department of Otorhinolaryngology. Patients were evaluated preoperatively and postoperatively at the third month. Degree of sialorrhea was assessed by The Drooling Frequency And Severity Scale (Thomas-Stonell and Greenburg classification), Teacher Drooling Scale, number of bibs or changed clothes per day and saliva wiping number per hour. Statistical analysis was performed using SPSS (Statistical Package for Social Sciences) for windows 16.0. Wilcoxon Singed-Rank tests were used to compare preoperative and postoperative measurements. The significance level was set at 0.05. Results: In all categories statistically significant differences (p=0.002) were found between preoperative and postoperative mean values over six months. One patient (%7.6) underwent urgent intervention because of postoperative hemorrhage. The postoperative result of method was successful in 12 patients (92,3) over all categories. However in one patient (%7,6) there was no changes in any category. Conclusion: Sialorrhea is a complex disorder benefiting by multidisciplinary approach. Surgical interventions are submandibular and/or parotid duct rerouting that diverts salivary flow or duct ligation, submandibular gland excision, tympanic neurectomy with or without chorda tympani section which decreases salivary secretion. Bilateral submandibular duct rerouting and sublingual gland excision combined with botulinum toxin type-A injection into the parotid gland is an effective and minimally invasive treatment with high parental satisfactory results. Key words: Sialorrhea, drooling, salivation, botulinum toxin, surgery, treatment, cerebral palsy, submandibular duct rerouting.
Approach to the patients with sialorrhea and treatment management
Amaç: Siyalore çeşitli sebeplerden kaynaklanabilen ağızdan sürekli ve kontrolsüz salya akmasıdır. Bu çalışmanın amacı siyaloreli çocuk hastalarda bilateral submandibular kanal relokasyonu ve sublingual bez eksizyonu ile birlikte parotis bezine botulinum toksin-A enjeksiyonunun etkinliğini değerlendirmektir. Çalışma Dizaynı: Retrospektif çalışma Bireyler ve Yöntem: Bu çalışma 2012-2016 yılları arasında Bezmialem Vakıf Üniversitesi Tıp Fakültesi Hastanesi Kulak Burun Boğaz Hastalıkları Kliniği'nde siyalore nedenli bilateral submandibular kanal relokasyonu ve sublingual bez eksizyonu ile birlikte bilateral parotis bezi içine botulinum toksin-A enjeksiyonu uygulanan 13 hasta dahil edilmiştir. Hastaların preoperatif ve postoperatif 3. ayda siyalore sıklık ve şiddetinin değerlendirilmesi (Thomas-Stonell ve Greenburg klasifikasyonu) ve öğretmen siyalore ölçeğinin değerlendirilmesi yapıldı. Ayrıca günlük önlük sayısı ve saatlik silme eylemi de sorgulanarak kaydedildi. İstatistiksel analizler için SPSS (Statistical Package for Social Sciences) for Windows 16.0 programı kullanıldı. Hastaların operasyon öncesi ve operasyon sonrası parametrelerinin karşılaştırılmasında Wilcoxon Signed-Rank testi kullanıldı. p<0.05 istatistiksel olarak anlamlı kabul edildi. Bulgular: Tüm parametrelerin değerlendirilmesinde preoperatif ve postoperatif değerler arasında anlamlı fark izlendi (p=.002). Hastaların birinde (%7,6) postoperatif hemoraji gelişti ve tekrar operasyona alındı. Siyalore sıklık skorlaması, siyalore şiddet skorlaması, öğretmen siyalore ölçeği değerleri, günlük değiştirilen önlük sayısı ve saatlik silme eylemi 12 hastada (%92,3) postoperatif en az bir değer düşerken, bir hastada (%7,6) hiç değişmemiştir. Sonuç: Siyalore multidisipiner yaklaşımdan fayda gören karmaşık bir sorundur. Cerrahi tedaviler; submandibular ve/veya parotis bezlerden gelen tükürüğü yönlendiren kanal relokasyonu ve tükürük miktarını azaltan kanal ligasyonu, submandibular bez eksizyonu ve korda timpani kesili veya kesisiz timpanik nörektomidir. Submandibular kanal relokasyonu ve sublingual gland eksizyonu ile birlikte bilateral parotis bezi içine botulinum toksin-A enjeksiyonu minimal invaziv, etkili ve hasta bakıcı memnuniyeti yüksek bir yöntemdir. Anahtar kelimeler: Siyalore, tükürük, botulinum toksini, cerrahi, tedavi, serebral palsi, submandibular kanal relokasyonu.
Keywords: MEDICINE; Kulak Burun ve Boğaz